Cropping history trumps fallow duration in long‐term soil and vegetation dynamics of shifting cultivation systems. Issue 2 (21st February 2017) - Wood, Sylvia L. R.; Rhemtulla, Jeanine M.; Coomes, Oliver T.
Abstract: In the study of shifting cultivation systems, fallow duration is seen as the key determinant of vegetation and soil dynamics: long fallows renew soil fertility, biomass, and biodiversity. However, long fallow systems are increasingly replaced around the world with short–medium fallow systems, and awareness is growing of the need to look across multiple (not just single) crop‐fallow cycles to accurately understand observed soil and vegetation patterns. In a study from Peru that builds on 50+ years of field‐level land‐use histories, we found that, over multiple crop–fallow cycles, farmers' cropping practices mattered more than fallow duration for biodiversity and soil fertility. After initial clearing of primary forest, a precipitous decline occurred in tree species richness of fallows (>50%) with gradual but continued loss thereafter (~0.5 species/yr), which resulted in shifts in species composition over time. For soils, the decline in fertility was more gradual with each additional cycle of cropping resulting in lowered soil organic matter, available phosphorus, and exchangeable sodium levels, even in fields with long fallow durations. In the most intensively used sites, soils experienced a 16% decline of soil organic matter over 4+ cycles. In contrast to previous studies, biomass accumulation and carbon stocks were not related to cropping history or to the number and duration of cycles observed. This suggests that biodiversity–soils–biomass dynamics may not necessarily "move together" in these systems. These results point to the importance of the number of crop–fallow cycles over fallow duration in driving soil fertility and vegetation dynamics under shifting cultivation in the Peruvian Amazon. Overtime shifting cultivation may erode soil fertility and biodiversity levels even if long fallows persist. As the decline in soils appears slow, it may be possible to address this effect with the use of amendments, however biodiversity declines and species compositional changes may be much harder to reverse.